EFFECT OF RED BEANS AND BLACK BEANS WITH A DIABETES MELLITUS: A SYSTEMATIC REVIEW - Pratiwi; Adi Magna Patriadi Nuhriawangsa; Tri Nugraha Susilawati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Diabetes mellitus is a chronic metabolic disease that requires dietary management. One of the diet strategies is a high consumption of antioxidants and fiber contained in red beans and black beans. The purpose of this article is to prove that red beans and black beans can treat diabetes mellitus. The method is a systematic review using the PRISMA protocol and JBI's Critical Appraisal Tools. The source of the article is experimental studies published in the last 10 years (2013-2023) in Google Scholar, Pubmed, and Science Direct databases. The results showed that red beans and black beans are rich in antioxidants and fiber. Antioxidants and fiber are known to reduce blood glucose levels and increase insulin levels. The conclusion of this article is red beans and black beans can treat diabetes mellitus. The suggestion of this review is that better to increase the daily dose of red beans and black beans consumption to treat diabetes.